(untitled) (Research, Society and Development, 2021)
Currently, research is advancing with low-intensity laser (LIL) in cells of the central nervous system, with the aim of evaluating the benefits of this therapy in neurological disorders such as Alzheimer’s, stroke, ischemia, epilepsy, among others. The aim of this study was to verify the biomodulatory and biostimulatory effects of LIL in neural cell culture. Diode laser at wavelength λ = 830 nm, power 40 mW, in continuous mode, was applied on the 9L/lacZ cell line with energy densities of 0.5 to 3 J/cm2. The analysis was performed 24 hours after irradiation, the results of cell viability showed a difference between the control and irradiated groups. As for the occurrence of apoptosis, no significant manifestation was observed between the control group compared to the irradiated group (P = 0.9956); there was a significant difference between apoptosis and death by necrosis between the control and treated groups (P<0.001). In the comet assay no statistically significant differences were observed. Regarding the objective of evaluating whether LIL promotes early activation of apoptosis or proliferation of 9L/lacZ cells at different energy densities of the infrared diode laser, we observed an increase in the number of neural cells, highlighting the action of biomodulation. Furthermore, LIL did not promote the activation of programmed cell death - apoptosis and did not show any indication of DNA damage by the comet assay. The results of this study are indicative that the laser in the near infrared has a positive interaction with neuronal cells.